2017
DOI: 10.1177/0961203317691370
|View full text |Cite
|
Sign up to set email alerts
|

Development of primary central nervous system lymphoma in a systemic lupus erythematosus patient after treatment with mycophenolate mofetil and review of the literature

Abstract: Primary central nervous system lymphoma (PCNSL) is a rare form of extranodal non-Hodgkin lymphoma and four cases of PCNSL have previously been described in association with mycophenolate mofetil. We report the fifth case of PCNSL in a patient with lupus nephropathy while on mycophenolate mofetil treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 7 publications
2
9
0
Order By: Relevance
“…Alternatively, the lymphoma may be secondary to chronic immunosuppression resulting in iatrogenic immune dysfunction . As observed in our second case, other patients treated with mycophenolate mofetil or infliximab for different conditions developed CNS B‐cell lymphoma . Finally, the chronic perivascular antigenic stimulation that occurs in the patients with CLIPPERS may lead to a malignant transformation of B cells targeting this antigen …”
Section: Discussionsupporting
confidence: 50%
“…Alternatively, the lymphoma may be secondary to chronic immunosuppression resulting in iatrogenic immune dysfunction . As observed in our second case, other patients treated with mycophenolate mofetil or infliximab for different conditions developed CNS B‐cell lymphoma . Finally, the chronic perivascular antigenic stimulation that occurs in the patients with CLIPPERS may lead to a malignant transformation of B cells targeting this antigen …”
Section: Discussionsupporting
confidence: 50%
“…Radiographic information was recorded in 7 patients and is summarized in Table 1 . [ 2 8 ] Among the 7 cases, 3 had multiple lesions. One lesion was infratentorial, while the others were supratentorial.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] Risk increases in patients with rheumatic diseases, partially due to the use of immunosuppressant. [ 2 ] Magnetic resonance imaging (MRI) manifestation is not specific to PCNSL and mimics other brain tumors. Herein, we reported a 39-year-old woman with systemic lupus erythematosus (SLE) who developed PCNSL after years of multiple immunosuppressant treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Given the strong association of PCNSL with immunosuppression, it has been hypothesized that increasing use of immunosuppressive medications to treat autoimmune conditions in older adults may be contributing to this trend (Villano et al , ; Shiels et al , ). Indeed, cases of PCNSL occurring among individuals with autoimmune disorders receiving immunosuppressive medications have been reported (Finelli, ; Balci et al , ). Herein, we utilized data from a large, nationally‐representative cohort of older adults (aged ≥65 years) to estimate associations between autoimmune conditions and PCNSL.…”
Section: Comparison Of the Characteristics Between Primary Cns Lymphomentioning
confidence: 99%
“…Population-based studies have shown that several autoimmune conditions are associated with increased risk of NHL due to either chronic inflammatory state, dysregulation and hyper-reactivity of B-cells along with impaired T-cell control, or immunosuppressants that are used for their treatment (Anderson et al, 2009;Fallah et al, 2014). PCNSLs have been previously reported in people with SLE (Balci et al, 2017) and myasthenia gravis (Finelli, 2005) and were attributed to receipt of long-term immunosuppressants, such as mycophenolate mofetil (for SLE) or azathioprine (for SLE, myasthenia gravis). In contrast, the association between uveitis and PCNSL may represent ocular manifestations of primary intraocular lymphoma (Chan et al, 2011).…”
mentioning
confidence: 99%